Het klinische domein van geestelijke zorgprofessionals - Schilderman, Hans (Religie & Samenleving, 2020)
This article aims to offer a contribution to the definition of the professional domain of spiritual care professionals working in clinical settings. Starting with a conceptual disentanglement of theology and religious studies in face of the issue of interreligious communication, a starting point for this definition is found in the humanities domain. Existential, developmental, and contextual dimensions of the human condition, each with topics of their own, are distinguished in defining the object of spiritual care. These topics require professional attention in a set of tasks that are subsequently presented. Next, it is argued that clinical pastoral education offers the proper post-master program to develop these tasks in an established clinical skills training program. Integration of clinical pastoral education in postmaster spiritual care apprenticeships offers the best condition to contribute and innovate spiritual care in clinical settings, so it is concluded.